Pengendalian Hipertensi secara Mandiri Melalui Penerapan Dietary Approaches to Stop Hypertension (DASH) Berbasis Aplikasi Android - Rozikhan Rozikhan (Fakultas Kesehatan Masyarakat Indonesia, 2026)
AbstractBackground: Hypertension, one of a non-communicable disease in many communities, evenbecoming a cause of death such as heart disease (45%) and stroke (51%). Hypertension cancausing cardiovascular, cerebrovascular and kidney disorders. The nonpharmacological therapyby diet control, reduce salt intake, add of amount potassium and magnesium intake, and physical exercise are recomended. The activity is a important to preventing hypertension complications.The recommended diet for hypertension patient is Dietary Approaches to Stop Hypertension(DASH). The development of health information systems through mobile devices makes itpossible to track cases of hypertension and help manage hypertension suffered. The aims of the study ware determine decreasing blood pressure in hypertensive patients by controllingindependently using an android application. Method: An experimental study with one grouppretest posttest design, located in Kumpulrejo Village, Kaliwungu District, Kendal Regency inAugust 2025. Sampling technique with accidental sampling, 30 respondents. The independentvariable is The DASH diet is an independent variable and dependengt variable is blood pressure.Data analyzed with paired t test. Results: The analysis test showed that there was a difference in systolic before and after treatment with p value of 0.001 < 0.05 which means that there was a significant decrease in systolic pressure before and after treatment. Diastole pressure also had a difference with p value of 0.016 < 0.05 which means there was a significant decrease.Conclusion: Intensive health education is highly recommended to increase self-assessment forhealthy life by applying daily DASH to help control blood pressure and prevent hypertensioncomplications.